Kindgdoms of Castile and Navarre. - Ortego-Rico, Pablo; Mugueta Moreno, Íñigo (Routledge, 2022)
The two political spaces analysed in this chapter (kingdoms of Castile and Navarre) dig their medieval roots in the Christian kingdoms formed in the north of the Iberian Peninsula between the eighth and the tenth centuries. The Kingdom of Castile (or Castile and León) was the successor of the small Kingdom of Asturias, which emerged in the northwest of the Iberian Peninsula in the eight century; it came to be known as the Kingdom of León after its territorial consolidation north of the Douro River in the tenth century. Its eastern frontier march, bordering with the valley of the Ebro, was the County of Castile, a de facto independent polity from the tenth century. For its part, the Kingdom of Pamplona (known as Kingdom of Navarre from 1162 onwards) was formed in the ninth century in the western Pyrenees, north of the Ebro, and became the dominant Christian polity in the Iberian Peninsula during the reign of Sancho III (1004-1035). After the death of this monarch in 1035, the territories that he had controlled through inheritance (Kingdom of Pamplona and counties of Aragón and Ribagorza) or marriage (County of Castile) were distributed among his children.
Política de acceso abierto tomada de: https://www.springernature.com/gp/open-research/policies/book-policies
Keywords: Castilla (Reino) - Política fiscal; Navarra (Reino) - Política fiscal; Castilla; Navarra; Historia medieval; Historia del Estado; Fiscalidad; Sistemas fiscales; Siglos XII-XV; Impuestos